2019
DOI: 10.1177/0898264319847818
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effect of Visual Impairment, Multimorbidity, and Frailty on Intrinsic Capacity in Community-Dwelling Older Adults

Abstract: Objectives: We aim to determine the prevalence of vision impairment (VI) and its cumulative impact on multimorbidity, frailty, physical and cognitive function, and quality of life. Method: In all, 780 community-dwelling older adults were interviewed for demographic data and a one-off physical activity screening. Covariate measurements include vision via Snellen chart, multimorbidity, five-item FRAIL (Fatigue, Resistance, Ambulation, Illnesses, & Loss of Weight) scale and Mini-Mental State Examination (MMSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Interestingly, no significant difference in handgrip strength was observed in individuals with a single sensory impairment compared with no impairment. Two other studies 38,40 also found no association between VI (both self‐reported and objectively measured) and weak handgrip strength; however, Vancampfort and associates 38 reported that individuals with HI (based on an interviewer's observation during the survey) had higher odds of weak handgrip strength (OR 1.40; 95% CI: 1.16 to 1.70; P < 0.001).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, no significant difference in handgrip strength was observed in individuals with a single sensory impairment compared with no impairment. Two other studies 38,40 also found no association between VI (both self‐reported and objectively measured) and weak handgrip strength; however, Vancampfort and associates 38 reported that individuals with HI (based on an interviewer's observation during the survey) had higher odds of weak handgrip strength (OR 1.40; 95% CI: 1.16 to 1.70; P < 0.001).…”
Section: Resultsmentioning
confidence: 95%
“…Four studies drew from Asian populations, seven from Caucasian populations and two from a combination of multiple ethnicities from six low‐ and middle‐income countries (LMIC). Two studies 30 , 38 had a moderate (NOS 5–7) and the remaining 22 , 23 , 28 , 29 , 31 , 32 , 33 , 34 , 39 , 40 , 41 ( n = 11) had a low (NOS ≥ 8) risk of bias ( Table 2 for longitudinal studies; Table 3 for cross‐sectional studies).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 39 articles describing 34 studies with 59,944 participants from six ASEAN countries were included in the review (Figure 1) as data from three cohorts were reported in several publications. (12)(13)(14)(15)(16)(17)(18)(19) Twenty-five studies were included in the meta-analysis. (14,17,18,)…”
Section: Resultsmentioning
confidence: 99%
“…And recently, a few studies have focused on these components together as IC composite concept in community-dwelling and nursing home older residents [14, 15]. The Healthy Older People Everyday (HOPE) study comprising 1,051 community-dwelling older adults revealed a combined effect of vision impairment, multimorbidity, and frailty on IC [14]. Another cohort study among Belgian nursing home residents showed that poor nutrition status and low balance performance, which composed of 2 domains of IC, predicted the incidence of 3-year mortality, and poor nutrition status also predicted 3-year autonomy decline [15].…”
Section: Introductionmentioning
confidence: 99%